Entrepreneurial strategy stimulating value creation: Conceptual findings and some empirical tests - Wojciech Dyduch (Entrepreneurial Business and Economics Review (EBER), 2019)
Objective: The objective of this article is to offer arguments for the strategic support of entrepreneurial processes that stimulate value creation. Recent findings show that firms concentrate mostly on outcomes and performance, neglecting the primary sources of value creation. As value is created largely from generating innovative ideas, it is important that firms strategically support the process of idea generation with the help of organisational design stimulating innovations, as well as strategic leadership. Research Design & Methods: The quantitative research using classical theory testing was adopted. Data was collected from organisations in Poland with a questionnaire and PAPI interviews. The data was assessed with descriptive statistics, factor analysis and correlation analysis. Findings: The research carried out identified four dimensions of the entrepreneurial strategy supporting value creation. The research indicated low but positive relations between strategic dimensions and subjective, non-financial measures of value creation and performance. Implications & Recommendations: For a higher level of new idea generation and innovativeness it is important to focus on innovation-friendly organisational design and on strategic leadership that stimulates network building for the use of external resources. Contribution & Value Added: The article offers arguments for the strategic support of innovativeness, it identifies empirical elements of entrepreneurial strategy, and indicates relations between them and non-financial assessment of value creation.
Keywords: L26; L10; 330; Entrepreneurial strategy; Value creation; Innovativeness